İslam hukuku açısından müşareke sukuku - Sylla, Mohamed (My University, 2019)
صكوك المشاركة و أحكامها في الفقه الإسلاميصكوك المشاركة أوراق مالية تصدر على أساس عقد المشاركة المعروفة في الفقه الإسلامي وتخضع لجميع أحكامها و ضوابطها. و تعتبر من أهم أدوات التمويل الإسلامي, إذ تستطيع الدول والمؤسسات المالية إصدارها لتمويل المشاريع الضخمة, التي يصعب على جهة واحدة تمويلها.و بناء على ما سبق تهدف الدراسة إلى تكوين رؤية و صورة شاملة واضحة و متكاملة حول صكوك المشاركة, معرفةً إياها, و مبينةً ماهيتها و أنواعها و خصائصها و الفروق الجوهرية بينها وبين غيرها من الأوراق المالية. و متطرقا إلى بيان آليات الإصدار و طرق التداول و الاسترداد و طرق توزيع الأرباح. كما تكفل البحث بدراسة الأحكام الفقهية المتعلقة بصكوك المشاركة موضحا ضوابط وحكم المسائل المتعلقة بالإصدار و التداول و الاسترداد و توزيع الأرباح و الخسائر. تطرقت كذللك إلى استعراض التجربة السودانية, مع تقديم مقترحات لتمويل المشاريع بصكوك المشاركة.وقد خلصت الدراسة إلى أنّ عملية إصدار صكوك المشاركة عملية هامة للنشاط الاقتصادي, و وسيلة فعالة في جذب و حشد الأموال, في حال عدم توافر السيولة لتمويل المشاريع. و لكن لا بد من توفّر الضوابط الشرعية فيها, و لذلك أصبح من الضروري عدم إصدار الصكوك إلا بعد موافقة اللجنة الشرعية.

SUKUKU AL-MUSHARAKA IN TERMS OF ISLAMIC LAWSukuk al-Musharaka (Deeds of participation) are issued on the basis of the participation contract known in Islamic jurisprudence and subject to all its’ provisions and regulation, and it is one of the most important tools of Islamic finance since Countries and financial institutions can use it to issue financing for large projects, which are difficult to be financed by individuals.Based on the above, the aim of this research is to create a clear and comprehensive picture of the participatory deeds, by giving definition of it, talk about its characteristics, types, and the fundamental differences between it and other types of financing methods. Also, referred to the statement of the tools of issuance, methods of trading and methods of distribution of profitsThe study also ensures the study of the jurisprudential provisions related to the Sukuk al-Musharaka clarifying the rules and regulations pertaining to issuance, trading, redemption and distribution of profits and losses.The research also reviewed the Sudanese experience, with proposals for financing projects with Deeds of participation and concluded that the process of issuing Sukuk al-Musharaka is an important process of economic activity and an effective means to attract and mobilize funds in the absence of means to finance projects.However it is necessary to have legal controls in it according to the sharia rules and regulations of financing and trading. Therefore, it became necessary not to issue Sukuk al-Musharaka without the approval of the Sharia Committee.
Keywords: Bonds; Contracts; Deeds; Investment; Islamic Financial; Islamic law; İslam hukuku; Sudan; Sukuk al-Musharaka; الاستثمار; التمويل الإسلامي; السودان Sukuk; الصكوك; العقود; سندات; صكوك المشاركة